Haematology of the Malaysian jungle fowl (Gallus gallus spadiceus) - Safar, Adnan; Babjee, Shaik Mohamed Amin (Universiti Pertanian Malaysia, 1985)
Haemotological values and total plasma protein concentration were determined from blood samples obtained from seven adult male jungle fowls (Gallus gallus spadiceus) trapped in the secondary forests of west Malaysia. The mean values for total RBC count, Rb concentration and PCV were 2.7 X 106/μl, 11.4 g/dl and 43.3% respectively. The mean values for MCV, MCR and MCRC were 159.4 μ3, 42.0 pg and 26.4% respectively. The mean of total WBC count was 27.5 X 103/μl. The mean differential and absolute counts for WBC were: heterophils, 51.3% and 14.0 X 103/μl; lymphocytes, 31.3% and 8.6 X 103/μl; monocytes, 8.6% and 2.5 X 103/μl; oesinophils, 4.3% and 1.2 X 10 3/f.Ll; and basophils, 4.6% and 1.2 X 103/μl. The mean total plasma protein concentration was 4.2 g/di This study shows that the jungle fowl has a higher,percentage of heterophils and lower percentage of lymphocytes than the domestic chicken.